Сарматське поховання на поселенні Лиса Гора - Кропотов, В.В. (Археологія, 2004)
Публікацію присвячено аналізу матеріалів нового пізньосарматського поховання другої половини II — першої половини III cm. н. е. з Нижнього Наддніпров'я. Скифское поселение IV в. до н. э. Лысая Гора расположено на левом берегу Каховского водохранилища в 1,5 км к северу от пгт Васильевка Запорожской обл. Сарматское захоронение было обнаружено на его западной окраине и ко времени раскопок на поверхности ничем не выделялось. Погребение было совершено в простой подпрямоугольной могиле, вытянуто головой на северо-восток и сопровождалось гончарным кубком, лепным горшком и бронзовой фибулой. Анализ погребального обряда и инвентаря позволяет отнести захоронение к позднесарматскому периоду и датировать второй половиной II — первой половиной III вв. н. э. Сарматские памятники того времени в Нижнем Поднепровье немногочисленны, и публикуемый комплекс дополняет их список. The Scythian settlement of the IV century BC called Lysaya Gora is situated on the left bank of the Kahovskoe reservoir, 1.5 km to the north of the urban village of Vasilievka in the Zaporizzya Region. The Sarmatian burial was discovered at its western edge and at the time of excavation it was inconspicuous on the surface. The burial oriented northeast was made in a simple almost rectangular grave, which contained a wheel-made beaker, a hand-made pot, and a bronze fibula. The analysis of the burial rite and the inventory makes it possible to associate this burial with the late Sarmatian Period and date it to the second half of the II — first half of III centuries AD. The Sarmatian monuments of this period in the lower reaches of the Dnieper River region are not numerous and publication of this assemblage expands their list.